2019
DOI: 10.3390/metabo9120295
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling Reveals the Difference on Reproductive Performance between High and Low Lactational Weight Loss Sows

Abstract: Sows suffering excess weight loss during lactation may delay weaning to estrus interval (WEI) and have a detrimental effect on subsequent reproductive performance, however, the underlying mechanism is not completely clear. Therefore, the goal of this study was to investigate physiological profiles manifested in plasma originating from high (HWL) and low lactational weight loss (LWL) sows. The plasma biochemical parameters, hormones, antioxidant parameters, and milk compositions were assessed. Furthermore, plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The samples were analyzed using a triple time-of-flight (TOF) mass spectrometer (ESI/Triple TOF 5600; AB Sciex, Concord, Canada) equipped with an electrospray ionization source used in positive and negative ion modes. The pretreatment, extraction, and identification of serum samples were according to the procedure described by Hu et al [ 27 ]. The raw data (whiff scan files) were converted into mzXML format using ProteoWizard [ 28 ] and were imported to the XCMS software for peak matching, retention time alignment, and peak area extraction [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples were analyzed using a triple time-of-flight (TOF) mass spectrometer (ESI/Triple TOF 5600; AB Sciex, Concord, Canada) equipped with an electrospray ionization source used in positive and negative ion modes. The pretreatment, extraction, and identification of serum samples were according to the procedure described by Hu et al [ 27 ]. The raw data (whiff scan files) were converted into mzXML format using ProteoWizard [ 28 ] and were imported to the XCMS software for peak matching, retention time alignment, and peak area extraction [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples were analyzed using a triple time-of-ight (TOF) mass spectrometer (ESI/Triple TOF 5600; AB Sciex, Concord, Canada) equipped with an electrospray ionization source used in positive and negative ion modes. The pretreatment, extraction, and identi cation of serum samples were according to the procedure described by Hu et al ( 2019) [27]. The raw data (whiff scan les) were converted into mzXML format using ProteoWizard [28] and were imported to the XCMS software for peak matching, retention time alignment, and peak area extraction [29].…”
Section: Determination Of Protein Levelsmentioning
confidence: 99%
“…This study found that sows supplemented with FFM had less BF and BW loss compared with those in the CON group. Additionally, the sows that lost excessive amounts of BW had extended weaning-to-estrous intervals (WEIs) [ 45 ]. The tendency for prolonged WEIs in the FFM group in this study suggests that the amount of fiber added may have been close to the maximum a sow can tolerate.…”
Section: Discussionmentioning
confidence: 99%